Participatory Modeling With QUICKScan to Shape Sustainable Urban Development - Verweij, Peter; Cormont, Anouk; Eupen, Michiel van; Winograd, Manuel; Hardoy, Jorgelina (Frontiers in Environmental Science, 2020)
Current spatial planning methods are often technocratic, slow, fail to use the right kind of evidence or do not involve (all) the actors needed to create support and consensus. We present a method that facilitates the use of evidence (data) in participatory spatial planning processes, resulting in a joint understanding of the most important causalities, as a means to build capacity across actors. QUICKScan is a participatory modeling method that links stakeholder- and decision maker knowledge and preferences to available spatial and spatio-statistical data, and is designed for group use in a multi-stakeholder workshop setting. We describe four urban QUICKScan applications, that vary in objective, scale and institutional setting. The most critical in organizing a QUICKScan session is to: (i) include crucial participants in a single plenary workshop (decision maker, local data expert, and local thematic experts), (ii) create an open atmosphere in which each and everyone's opinion is treated equally, (iii) dialogue is more important than an abundance of detailed spatial data, and (iv) start with simple modeling rules and iterate often while expanding the set of rules and trying out alternatives.